2014
DOI: 10.1016/j.febslet.2014.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum to “The dark sides of amyloid in Alzheimer's disease pathogenesis” [FEBS Lett. 588 (5) (2014) 641–652]

Abstract: On page 642, paragraph 2, right column, line 12 the following reference should be inserted: [170]. Sorrentino, G. and Bonavita, V. (2007) Neurodegeneration and Alzheimer's disease: the lesson from tauopathies. Neurol. Sci. 28, 63-71.The first 19 lines of paragraph 4.2, on page 645, should read: ''APP seems to have a role in neural degeneration mostly as it is processed, rather than through Ab formation [15]. For instance, there is now broad evidence of the neuroprotective and neuroproliferative role of sAPPa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It has been shown that the level of ACh receptors is reduced in AD and that cellular dysfunction and imbalance in neurotransmitter signaling could be responsible for the symptoms of AD. 36 Fig. 6(C) shows the quantification of ACh concentration after 5 days of culture with neural network formation in the static/ dynamic system and with/without 5 μM Aβ addition for 3 days.…”
Section: Comparison Of Synapse Formation Synaptic Functionality and A...mentioning
confidence: 99%
“…It has been shown that the level of ACh receptors is reduced in AD and that cellular dysfunction and imbalance in neurotransmitter signaling could be responsible for the symptoms of AD. 36 Fig. 6(C) shows the quantification of ACh concentration after 5 days of culture with neural network formation in the static/ dynamic system and with/without 5 μM Aβ addition for 3 days.…”
Section: Comparison Of Synapse Formation Synaptic Functionality and A...mentioning
confidence: 99%
“…1,2 Although the precise mechanism leading to the development of AD has not been completely elucidated, the formation of Ab aggregates is widely accepted as the initial neurodegenerative event in AD brains. 3,4 Therefore, the in vivo detection of Ab plaques with molecular imaging techniques is expected to lead to the early diagnosis of AD and facilitate the discovery of effective therapeutic agents for it. 5,6 Molecular imaging techniques for the in vivo imaging of Ab plaques mainly include positron emission tomography (PET) and single photon emission computed tomography (SPECT) using radioactive probes, and optical imaging using uorescent probes.…”
Section: Introductionmentioning
confidence: 99%